2019
DOI: 10.5812/semj.semj-81460
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Workload and Needlestick Injuries Among the Nurses in the Hospitals Affiliated with Ahvaz University of Medical Sciences

Abstract: Background: This study investigated the workload and its effects on the prevalence of needlestick injuries (NSIs) among the nurses in the hospitals affiliated with Ahvaz University of Medical Sciences (AUMS). Methods: In this cross-sectional study, 416 registered nurses working in different wards of the hospitals affiliated with Ahvaz University of Medical Sciences (AUMS) were randomly selected. Data collection instruments were a demographic questionnaire and NASA-TLX workload questionnaire. Results: The preva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The results of this study showed that the mental workload of the studied nurses is generally high with an average of 71.05. In several studies, the mental workload of nurses has been evaluated as high (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study showed that the mental workload of the studied nurses is generally high with an average of 71.05. In several studies, the mental workload of nurses has been evaluated as high (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%